Kontrol Methanogenesis Pada Ruminansia Dan Kontribusinya Terhadap Pencegahan Polusi Lingkungan - B. Santoso; Th. Sraun (Universitas Andalas, 2006)
Methane (CH4) is produced as a result of anaerobic fermentation of the soluble and structural carbohydrates by methanogens in the rumen of ruminant animals, which is released into the environment by eructation. Methane production from ruminant range from 2 to 12% of the gross energy intake and represents a substantial loss in efficiency of animal production. Recently, CH4 production by ruminants has also received attention due to its contribution to global warming. Much research has been carried out on the manipulation of rumen fermentation to inhibit methanogenesis. Several strategies can be treated to reduce CH4 production in the rumen such as by feed manipulation (composition, feeding level) or by the use of both chemical and natural feed additives. More biotechnological interventions e.g., defaunation, probiotics and prebiotics, and introduction of reductive acetogenesis in the rumen, are also mentioned. Chemical inhibitors have proved to be effective in decreasing CH4 production to variying degrees. Problems with chemical inhibitors have been noted, such as rumen microbial adaptation, toxicity to the host, residues in endible products and an inability to increase energetic efficiency.